2020
DOI: 10.1002/jbmr.4566
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of PTH 1-34 and 1-84 Therapy in Chronic Hypoparathyroidism: A Meta-Analysis of Prospective Trials

Abstract: Hypoparathyroidism is the only endocrine deficiency for which hormone replacement therapy is not the standard of care. Although conventional treatments may control hypocalcaemia, other complications such as hyperphosphatemia, kidney stones, peripheral calcifications, and bone disease remain unmet needs. This meta‐analysis (PROSPERO registration number CRD42019126881) aims to evaluate and compare the efficacy and safety of PTH1−34 and PTH1−84 in restoring calcium metabolism in chronic hypoparathyroidism. EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 84 publications
(339 reference statements)
0
2
0
Order By: Relevance
“…Human recombinant parathyroid hormone (rhPTH) represents a potential successful treatment of hypoparathyroidism in pediatric patients as it has demonstrated positive impacts on phosphatemia, Ca–P product, and hypercalciuria [ 22 , 23 , 24 , 25 , 26 ], but further studies are required [ 23 ] as currently no consensus on ADH1 treatment exists. However, this treatment carries a theoretical risk of osteosarcoma, which remains unconfirmed in human studies [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human recombinant parathyroid hormone (rhPTH) represents a potential successful treatment of hypoparathyroidism in pediatric patients as it has demonstrated positive impacts on phosphatemia, Ca–P product, and hypercalciuria [ 22 , 23 , 24 , 25 , 26 ], but further studies are required [ 23 ] as currently no consensus on ADH1 treatment exists. However, this treatment carries a theoretical risk of osteosarcoma, which remains unconfirmed in human studies [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…34 Hypoparathyroidism lacks standard hormone replacement therapy, and conventional treatments may not fully address complications like hyperphosphatemia, peripheral calcification, kidney stones, and bone disease. 35 Therefore, teriparatide has been considered as a potential treatment option to treat the same. In a 3-year randomized trial involving 27 patients with hypoparathyroidism, twice-daily teriparatide was found to effectively maintain normal serum calcium levels without hypercalciuria, providing a safe alternative to calcitriol therapy.…”
Section: Hypoparathyroidismmentioning
confidence: 99%